IDENTIFIKASI KANKER PAYUDARA DENGAN THERMAL - Titik Nurhayati; Dinar Mutiara K.N; Budiani Destyningtias (Prosiding SNST Fakultas Teknik, 2010)
Cancer is one of the causes of the main death in South-East Asian countries. Cancer is become 6th rank cause of the death in Indonesia. Around 800,000 Indonesia peoples indicated cancer per year.This research seeks for an alternatif method and tools for indicating breast cancer.The method of this research is using Fluke Thermal Ti20and thermal imager.Keyword : breast cancer, cropping, histogram.